Comparative study of Dapagliflozin versus Glimepiride effect on insulin regulated aminopeptidase (IRAP) and interleukin-34 (IL-34) in patient with type 2 diabetes mellitus - Rania Zekry; Gamal A. Omran; Nashwa M. El-Gharbawy; Rehab H. Werida (Scientific Reports, 2023)
Abstract Type 2 diabetes mellitus (T2DM) is one of the most common diseases, that managed by several medications such as Glimepiride and Dapagliflozin. This study aims to compare the effects of Dapagliflozin versus Glimepiride on glycemic control, insulin resistance, and biomarkers as (extracellular domain of insulin regulated aminopeptidase) IRAPe, (interleukin-34) IL-34, and (N-terminal pro b-type natriuretic peptide) NT-proBNP. This study included 60 type 2 diabetic patients, who are randomized to receive either Glimepiride 4 mg/day (group 1) or Dapagliflozin 10 mg/day (group 2). Blood samples were collected at baseline and after 3 months of treatment for biochemical analysis. Additionally, HOMA-IR is calculated. After 3 months of receiving the intervention, there is no significant difference between the effects of Glimepiride and Dapagliflozin on FBG, PPBG, HbA1C%, fasting insulin, and HOMA-IR. The difference between both groups is significant for IL-34 (p = 0.002) and non-significant for IRAPe (p = 0.12) and NT-Pro BNP (p = 0.68). Both Glimepiride and Dapagliflozin significantly improve glycemic control, and HOMA-IR with no significant difference between them. Both drugs significantly improved the level of NT-proBNP. Dapagliflozin has a borderline significant effect on IRAPe but not IL-34, and Glimepiride has significant effect on IL-34 but not IRAPe. Clinical Trial Registration: This trial was registered on clinicaltrial.gov (NCT04240171).